Catalytically active inclusion bodies of cold-adapted lipase: production and its industrial potential - Bello, Muhammad Nura; Sabri, Suriana; Mohd Yahaya, Normi; Mohd Shariff, Fairolniza; Mohamad Ali, Mohd Shukuri (Springer Science and Business Media Deutschland GmbH, 2025)
Heterologous overexpression of certain recombinant proteins in E. coli often triggers the formation of inclusion bodies (IBs). Traditionally viewed as inactive aggregates, IBs are now known to sometimes retain native-like folding and catalytic activity, termed catalytically active inclusion bodies (CatIBs). In this work, we investigated the CatIBs formed by recombinant LipAMS8, a cold-adapted lipase from an Antarctic Pseudomonas sp., expressed in E. coli iBL21(DE3)/pET32b. Overexpression yielded abundant insoluble aggregates which were gently isolated using 50 mM Tris–HCl, 50 mM NaCl, 1% Triton X-100 (pH 8.0), and subsequently solubilized in Tris–HCl (pH 8.0) without denaturants. Scanning electron microscopy revealed rod-like protein particles ranging from ~ 100 nm up to 1 μm. Biochemical characterization demonstrated that these LipAMS8 aggregates indeed function as CatIBs, exhibiting enzymatic activity with a defined optimum temperature, broad pH stability, specific metal ion responses, and remarkable tolerance to organic solvents. The LipAMS8 CatIBs retained significant residual activity (≥ 50%) across a wide pH range and various temperatures and showed only modest activity loss after prolonged storage (over 13 weeks at 4 °C and 8 weeks at 25 °C, maintaining > 50% activity). Notably, these aggregates displayed higher stability in extreme conditions (pH and organic media) compared to typical soluble enzymes. This study is the first to characterize a naturally formed lipase CatIB, highlighting that LipAMS8 CatIBs are produced in vivo without any artificial tags. The LipAMS8 CatIBs combine high catalytic activity with exceptional stability and solvent tolerance, underscoring an alternative strategy to obtain cold-active lipases in immobilized form. Such robust CatIB biocatalysts are highly sought after in industries for diverse biotransformations in challenging conditions.